Implantação do Lean Office no Departamento de Engenharia e Projetos de uma cooperativa agroindustrial - Albanez, Izabelle Pazinato (2023)
The concept of Lean, or lean production, aims to eliminate waste in your production line. Just like in manufacturing, the flow of information in offices can present stages considered waste, and the race to eliminate these factors is essential for companies in the sector to become more competitive. The work presents a process innovation through the implementation of one of the aspects of Lean Manufacturing, the Lean Office, within the engineering and projects department of an agro-industrial cooperative. In this sense, this work sought to identify waste in the administrative process, based on the application of the principles of the lean Lean Office methodology, using value stream mapping (MFV), based on the Makigami model. The value stream chosen was the engineering study request process. In principle, data relating to the chosen process was collected to create a mapping of the value stream, listing waste and points for improvement. Thus, action plans were proposed containing solutions that aimed to increase added value and reduce waste, with the expectation that a future application will attest to the expected improvement in the processing time of activities, with a 44% reduction in the time spent since preparing the request form until approval of the investment demand. The area of Business Intelligence and all sectors that involve data analysis are in evidence, especially when it is reflected in the improvement of process management and, consequently, provides ease and assistance in decision making. Power BI is an example of a tool that handles this data effectively and contributes to improving business performance. This study also presents, as a lean Office visual management tool, the implementation of a dashboard, using Power BI, as a tool to facilitate control, monitoring and data analysis. As a result of this investigation, it is clear that the principles of Lean, originally used only in manufacturing, also prove to be efficient when applied in other work environments, providing good results for the company's administrative sector.